FLUKTUASI INVESTASI KOREA SELATAN DI INDONESIA TAHUN 2011-2015 - Afyani (HI 16 UMY 100, 2016)
*100 The relation between Indonesia-South Korea started since 1973 with opened dilpomatic relation between both state. This relation both country is who complete each other, indonesia had rich in natural resources, and cheap labor but south korea has sophisticated technology, capital and good maintain. This investment relation become better since assigned Joint Declaration by presidents on 4th of December 2006. Indonesia-south korea have an interest. Beside finacial benefit, Korea is one of indonesia important tranding partners. Indonesia-Korea have been closely cooperating in many areas including economic development, information technology, foreign workers, energy, est. In 2011, Indonesia–South Korea concluded Joint Study Group to strengthen the relation both state in filed of trade and investment in form Comprehensive Economic Partnership Agreement. But in 2014, the realization of investment South Korea in Indonesia decreased from US$ 2,2 billion in 2013 to US$ 1,1 billion. The question is why IK-CEPA made the investment of South Korea in Indonesia undergo fluctuation. Keyword: Joint Study Group, IK-CEPA, Investment